Genetic connectivity across marginal habitats: the elephants of the Namib Desert. Issue 17 (3rd August 2016) - Ishida, Yasuko; Van Coeverden de Groot, Peter J.; Leggett, Keith E. A.; Putnam, Andrea S.; Fox, Virginia E.; Lai, Jesse; Boag, Peter T.; Georgiadis, Nicholas J.; Roca, Alfred L.
Abstract: Locally isolated populations in marginal habitats may be genetically distinctive and of heightened conservation concern. Elephants inhabiting the Namib Desert have been reported to show distinctive behavioral and phenotypic adaptations in that severely arid environment. The genetic distinctiveness of Namibian desert elephants relative to other African savanna elephant ( Loxodonta africana ) populations has not been established. To investigate the genetic structure of elephants in Namibia, we determined the mitochondrial (mt) DNA control region sequences and genotyped 17 microsatellite loci in desert elephants ( n = 8) from the Hoanib River catchment and the Hoarusib River catchment. We compared these to the genotypes of elephants ( n = 77) from other localities in Namibia. The mtDNA haplotype sequences and frequencies among desert elephants were similar to those of elephants in Etosha National Park, the Huab River catchment, the Ugab River catchment, and central Kunene, although the geographically distant Caprivi Strip had different mtDNA haplotypes. Likewise, analysis of the microsatellite genotypes of desert‐dwelling elephants revealed that they were not genetically distinctive from Etosha elephants, and there was no evidence for isolation by distance across the Etosha region. These results, and a review of the historical record, suggest that a high learning capacity and long‐distance migrations allowed Namibian elephants to regularly shift their ranges to survive in the face of high variability in climate and in hunting pressure. Abstract : Elephants inhabiting the Namib Desert are said to display behavioral and phenotypic adaptations to the severely arid environment, but their genetic distinctiveness has not been established. We genotyped African savanna elephants ( Loxodonta africana ) across Namibia, finding that desert‐dwelling elephants are genetically similar to elephants at Etosha and other nearby localities, and finding that no signal of isolation by distance was present across Etosha. A high learning capacity and long‐distance migrations have allowed Namibian elephants to survive in the face of considerable variability in local climate and in hunting pressure. Picture courtesy of V. E. Fox.